Estimation of blight and spot diseases severity in Ciherang and Ciliwung rice varieties based on vegetation index algorithms - LA ODE SANTIAJI BANDE; ASMAR HASAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bande LOS, Hasan A. 2024. Estimation of blight and spot diseases severity in Ciherang and Ciliwung rice varieties based on vegetation index algorithms. Biodiversitas 25: 1015-1021. Blight and spot diseases are often associated with rice plant, causing high disease severity and potentially reducing crop production. One effective disease management strategy is using resistant varieties and intensive disease monitoring through camera sensor technology and vegetation index-based image processing. Therefore, this study aimed to assess the severity of blight and spot diseases on two rice plant varieties based on vegetation indexes. Image recording was carried out on rice field and leaf samples of Ciherang and Ciliwung varieties. This was followed by image processing based on normalized difference vegetation index (NDVI) to determine the proportion of sick/healthy plants in the field and dark green color index (DGCI) to quantify disease severity. The results showed that the proportion of healthy plant in Ciliwung rice field was greater than in Ciherang as shown by NDVI. Based on DGCI, Ciliwung also had a relatively lower level of disease severity compared to Ciherang, although the difference was not statistically significant. Blight disease caused more severe damage to rice leaf than spot disease based on image processing results. Furthermore, a positive correlation was observed between the increase in DGCI and NDVI.